Peculiarities of studying abstract translation by engineering students - Ponikarovska, Svitlana; Понікаровська, Світлана Володимирівна (Харківський національний автомобільно-дорожній університет, 2023)
The article studies the task of teaching abstract translation to students of non-phi lology majors. Goal. There are two types of translation – written and oral. Having a common goal, they nevertheless take place in completely different conditions. Engineering students have limited time to study translation. The purpose of this article is to focus on the features of referential translation as something that can be mastered with the available number of hours. Methodology. The purpose and specifics of the research made necessary to use the description method with elements of comparative analysis for comprehensive coverage of the issue. During the translation of a written text, the translator can put the text aside for some time and return to it later, he can use dictionaries, consult with specialists and eventually completely edit the text, which forces the author to focus on the written language, in particular, abstract translation to clearly outline its mechanism and goals, as it is a more achievable prospect for future engineers. Results. Abstract translation is a creative process that includes the con tent of written texts and a summary of the content of the referenced material. This process teaches stu dents to summarize information concisely. Referencing teaches not only a meaningful approach to the text with the extraction of the most relevant information, but also develops written communication skills, enriches the vocabulary of scientific and technical special vocabulary, terminology, and introduces the extralinguistic realities of the country whose language is being studied. The article emphasized the pe culiarities of this process. Originality. The article deals with special requirements for abstracting texts in another language. They should be semantically adequate, limited to a small volume, and at the same time describe the main content of the primary document as fully as possible. Practical value. The article contains several tips on teaching referential translation, several examples of exercises for the formation of the necessary knowledge and skills.
Особливості вивчення рефератного перекладу студентами інженерного фаху
Keywords: abstract translation; knowledge; abstract; text; editing; mechanism; переклад реферату; редагування; реферування; текст; механізм; знання; 378.147; 10.30977/BUL.2219-5548.2023.102.0.120